1991
DOI: 10.3109/02841869109091804
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Gastrointestinal and other Primary Malignant Diseases Following Gastric Cancer

Abstract: The risk of developing a second primary cancer was studied among 34,506 gastric cancer patients identified through the Swedish Cancer Registry. A second cancer was reported in 962 patients compared to an expected number of 826 (relative risk = 1.16, 95% confidence limits = 1.09-1.24). The slightly but significantly elevated risk was largely confined to the first year after the gastric cancer diagnosis, and to patients under 70 years old at the time of diagnosis. The risk was significantly increased for cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 1 publication
5
17
1
Order By: Relevance
“…In that study, the incidence of synchronous and metachronous cancer in patients with gastric cancer was 2.0% in Japan. Since then, other studies have reported an incidence of 1.1-4.7% [11][12][13][14][15][16][17]. In this study, the incidence was 3.4%, but it seems to be underestimated, as the study excluded those patients who were not operated on for gastric cancer due to the inoperability of their advanced gastric cancer stage.…”
Section: Discussionmentioning
confidence: 38%
“…In that study, the incidence of synchronous and metachronous cancer in patients with gastric cancer was 2.0% in Japan. Since then, other studies have reported an incidence of 1.1-4.7% [11][12][13][14][15][16][17]. In this study, the incidence was 3.4%, but it seems to be underestimated, as the study excluded those patients who were not operated on for gastric cancer due to the inoperability of their advanced gastric cancer stage.…”
Section: Discussionmentioning
confidence: 38%
“…In patients with gastric carcinoma, the prevalence of associated primary carcinomas reported by several authors varies between 2.8% [18] and 6.8% [5]. In Japan, Yoshino et al [19] found multiple primary carcinomas combined with gastric carcinomas in 2.1% of patients with apparently single gastric carcinomas.…”
Section: Discussionmentioning
confidence: 98%
“…In particular, a metachronous CRC after surgery for GC, and a metachronous GC after surgery for CRC were often found (23,24). There have been no reports to our knowledge on the biological nature or characteristics of any specified carcinoma with double carcinomas of the stomach and colorectum.…”
Section: Discussionmentioning
confidence: 99%